Isopsoralen Improves Glucocorticoid-induced Osteoporosis by Regulating Purine Metabolism and Promoting cGMP/PKG Pathway-mediated Osteoblast Differentiation - Liu, Defeng; Ma, Lingyun; Zheng, Jihui; Zhang, Zhenqun; Zhang, Nana; Han, Zhongqian; Wang, Xuejie; Zhao, Jianyong; Lv, Shuquan; Cui, Huantian (Current drug metabolism, 2024)
The effects of Isopsoralen (ISO) in promoting osteoblast differentiation and inhibiting osteoclast formation are well-established, but the mechanism underlying ISO's improvement of Glucocorticoid- Induced Osteoporosis (GIOP) by regulating metabolism remains unclear. This study aims to elucidate the mechanism of ISO treatment for GIOP through non-targeted metabolomics based on ISO's efficacy in GIOP. Initially, we established a GIOP female mouse model and assessed ISO's therapeutic effects using micro-CT detection, biomechanical testing, serum calcium (Ca), and phosphorus (P) level detection, along with histological analyses using hematoxylin and eosin (HE), Masson, and tartrate-resistant acidic phosphatase (TRAP) staining. Subsequently, non-targeted metabolomics was employed to investigate ISO's impact on serum metabolites in GIOP mice. RT-qPCR and Western blot analyses were conducted to measure the levels of enzymes associated with these metabolites. Building on the metabolomic results, we explored the effects of ISO on the cyclic Guanosine Monophosphate (cGMP)/Protein Kinase G (PKG) pathway and its role in mediating osteoblast differentiation. Our findings demonstrate that ISO intervention effectively enhances the bone microarchitecture and strength of GIOP mice. It mitigates pathological damage, such as structural damage in bone trabeculae, reduced collagen fibers, and increased osteoclasts, while improving serum Ca and P levels in GIOP mice. Non-- targeted metabolomics revealed purine metabolism as a common pathway between the Control and GIOP groups, as well as between the ISO high-dose (ISOH) group and the GIOP group. ISO intervention upregulated inosine and adenosine levels, downregulated guanosine monophosphate levels, increased Adenosine Deaminase (ADA) expression, and decreased cGMP-specific 3',5'-cyclic phosphodiesterase (PDE5) expression. Additionally, ISO intervention elevated serum cGMP levels, upregulated PKGI and PKGII expression in bone tissues, as well as the expression of Runt-related transcription factor 2 (Runx2) and Osterix, and increased serum Alkaline Phosphatase (ALP) activity. In summary, ISO was able to enhance the bone microstructure and bone strength of GIOP mice and improve their Ca, P, and ALP levels, which may be related to ISO's regulation of purine metabolism and promotion of osteoblast differentiation mediated by the cGMP/PKG pathway. This suggests that ISO is a potential drug for treating GIOP. However, further research is still needed to explore the specific targets and clinical applications of ISO.